Potential of agroforestry orchards as a conservation set-aside initiative in industrial rubber tree and oil palm plantations for avian biodiversity - Yahya, Muhammad Syafiq; Sharifah Nur Atikah; Mukri, Izereen; Oon, Aslinda; Ainil Hawa; Sanusi, Ruzana; Norhisham, Ahmad Razi; Lechner, Alex M.; Azhar, Badrul (Springer, 2023)
At the expense of irreversible biodiversity loss, industrial modern agriculture is expanding in tropical regions. The conversion of forests to large scale monoculture plantations has fragmented and reduced habitat complexity, and altered biotic communities. However, the establishment of agroforestry orchards as a part of a conservation set-aside programme may aid biodiversity by providing a wider range of ecological niches to support more diverse bird fauna within industrial monoculture plantations. Thus, in this study, we compared avian biodiversity assemblages (species richness, abundance, and functional bird groups) between two types of agricultural production (agroforestry orchards and agriculture monocultures) in Peninsular Malaysia with the aim of assessing the applicability of the conservation set-aside. We measured 14 predictor variables consisting of habitat attributes, vegetation health, and insect food availability, to determine the key ecological drivers for avian biodiversity in tropical agriculture matrices. Across the study area, we recorded 6,284 birds from 110 species (42 families) via point count sampling. Our results revealed that agroforestry orchards were able to support greater avian biodiversity assemblages in terms of species richness and abundance compared to monoculture plantations. Bird species richness and abundance were driven by 10 out of 14 predictor variables, with arthropod order richness, vegetation health, land-use type and season having significant influence on both models. Bird functional groups were attributed to 11 predictor variables with vegetation health, land-use type and season having the most influence over all bird groups. Our findings highlight the potential of agroforestry orchards as conservation setaside for avian biodiversity in industrialised monoculture plantation landscapes